A little ray of sunshine - Higgins, Kristan (Berkley, 2023)
"Harlow Smith thought she had finally achieved the quiet life she wanted-a little bookstore on Cape Cod, an apartment in her grandpa's house, a more or less happily single life-when the biggest secret from her past walked into town and changed everything. A kid walks into your bookstore and says to you, Guess what? I'm your son. The one you put up for adoption seventeen years ago. The one you never told anyone about. Surprise! His name is Matthew Walker, and he's come to spend the summer on the Cape with his parents. Why? Well, he wants to meet you before he heads off to college in the fall. Tiny detail-he didn't tell his adoptive parents about his plan. And while you hoped this day would come someday, you're so stunned, you actually faint. You're overjoyed (and stunned) and worried (and stunned) and you've yearned to meet him, but you didn't know it would be like this. Did you mention feeling stunned? Even more gobsmacked is your family. The Smiths looked like (and thought they were) the perfect family in town. How could Harlow, the "boring sister" who runs the bookstore with her dotty old grandfather, have a secret baby? How did she keep this secret for so long? More than the truth of that baby will come out over the summer ahead, a summer filled with emotion as more than one secret is revealed, long-lost hurts are discovered...and one slightly lost soul realizes the best of everything is yet to come"--